2014
DOI: 10.1111/2049-632x.12139
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm formation and treatment in soft tissue fillers

Abstract: Injection of soft tissue fillers plays an important role in facial reconstruction and esthetic treatments such as cosmetic surgery for lip augmentation and wrinkle smoothening. Adverse events are an increasing problem, and recently, it has been suggested that bacteria are the cause of a vast fraction these. We developed a novel mouse model and evaluated hyaluronic acid gel, calcium hydroxyl apatite microspheres, and polyacrylamide hydrogel for their potential for sustaining bacterial infections and their possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 29 publications
(37 reference statements)
1
47
0
Order By: Relevance
“…The viscous mucus is the perfect habitat for bacterial growth and biofilm development and facilitates persistent bacterial infection (Bjarnsholt et al 2009a;Johansen et al 2012). The presence of foreign bodies including artificial joints and indwelling catheters also support the advent of chronic biofilm infections , and we have found that the same is also true for injected tissue fillers (Alhede et al 2014;Bjarnsholt et al 2009b;Christensen et al 2013). Acquired chronic diseases such as diabetes mellitus, arteriosclerosis of leg arteries, and smoking-induced chronic obstructive pulmonary disease (COPD) also create perfect habitats for chronic bacterial infections as seen in COPD patients, who are prone to chronic lung infections or patients suffering from non-healing wounds, which are chronically infected with…”
Section: Referencessupporting
confidence: 71%
See 1 more Smart Citation
“…The viscous mucus is the perfect habitat for bacterial growth and biofilm development and facilitates persistent bacterial infection (Bjarnsholt et al 2009a;Johansen et al 2012). The presence of foreign bodies including artificial joints and indwelling catheters also support the advent of chronic biofilm infections , and we have found that the same is also true for injected tissue fillers (Alhede et al 2014;Bjarnsholt et al 2009b;Christensen et al 2013). Acquired chronic diseases such as diabetes mellitus, arteriosclerosis of leg arteries, and smoking-induced chronic obstructive pulmonary disease (COPD) also create perfect habitats for chronic bacterial infections as seen in COPD patients, who are prone to chronic lung infections or patients suffering from non-healing wounds, which are chronically infected with…”
Section: Referencessupporting
confidence: 71%
“…It is still argued, however, that tissue fillers do not support bacterial growth (Alijotas-Reig et al 2010). To investigate this further researcher incubated different relevant bacteria (including S. epidermidis and P. acnes) with different tissue fillers in an in vitro setup (Alhede et al 2014). They found that non-degradable as well as slowly degradable and degradable fillers were able to nest bacterial biofilms (see Fig.…”
Section: Tissue Fillers and Bacterial Growthmentioning
confidence: 99%
“…Recognition of the potential for adverse events contributes to the need for a judicious approach in applying optimal bolus volumes to achieve the desired effect. 34 The investigators emphasize the importance of not exceeding bolus volumes of 0.1-0.2 mL. Important factors, including slow and deliberate technique, smooth movement of the needle through the tissue, amount of filler injected, positions and plane of injection, and the overall experience and skill of the injecting physician, may impact safety and the incidence of complications that commonly occur with the use of all HA fillers.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These quiescent communities may become activated on repeated treatment. The surface area of product (large bolus), longevity of product, 16,17 and inadequate sterile technique are other factors hypothesized to play a role in biofilm development. In the panel’s opinion, hyaluronic acid fillers have a low incidence of biofilm formation, although the relative risk may vary by filler, and the risk may be increased if the product is placed in the presence of a previously injected permanent filler.…”
Section: Complication Management Is the Largest Unmet Need With Hyalumentioning
confidence: 99%